THE EFFECT OF LISINOPRIL ON BLOOD GLUCOSE LEVEL - Qureshi, Khalid Mahmood; Ahmed, Raja Zafar; Khan, Misbahul Islam; Pasha, Nusrat (Journal of Ayub Medical College Abbottabad, 1998)
Khalid Mahmood Qureshi, Raja Zafar Ahmed, Misbahul Islam Khan, Nusrat Pasha The aim of this study was to evaluate the effect of lisinopril on glucose metabolism in mild to moderate hypertensive non-insulin dependent diabetic patients. One hundred and twenty patients were divided into two groups. Group-A was given placebo of lisinopril for two weeks. Group-B was given lisinopril in a fixed dose of 10 mg once daily for two weeks. Comparison of fasting blood glucose levels before and after the treatment showed that the blood glucose level was almost unchanged.